Cuban Educational Association of the United States of America records - Cuban Educational Association of the United States of America
Correspondence, application forms, rosters, scrapbooks, financial records, photographs of students, and other records pertaining to the work of the Cuban Educational Association of the United States of America and to students aided by the association. Primarily correspondence of Gilbert K. Harroun, secretary-treasurer, and of his assistant, Laura D. Conger. Correspondents include representatives of schools, colleges, and universities; Cubans and Puerto Ricans seeking the aid of the association; and John Jacob Astor, Nicholas Murray Butler, Seth Low, Theodore Roosevelt, Albert Shaw, Joseph Wheeler, and Leonard Wood.
Educational association founded in 1898 to assist Cuban and Puerto Rican students securing an education in the United States. Dissolved in 1903.
Collection material in English and Spanish.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Astor, John Jacob, -- 1864-1912 -- Correspondence; Butler, Nicholas Murray, -- 1862-1947 -- Correspondence; Conger, Laura D. -- Correspondence; Harroun, Gilbert K. -- 1835-1901 -- Correspondence; Low, Seth, -- 1850-1916 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Shaw, Albert, -- 1857-1947 -- Correspondence; Wheeler, Joseph, -- 1836-1906 -- Correspondence; Wood, Leonard, -- 1860-1927 -- Correspondence; Cubans -- Education -- United States; Education -- United States; Puerto Ricans -- Education -- United States; Students, Foreign -- United States